Sociological perspectives for the study and analysis of educational organizations - Paniago, Rosenilde Nogueira; Nunes, Patrícia Gouvêa; Pamplona, Renata Silva; Sarmento, Teresa; Moraes, Simone de Sousa (Advances in Social Sciences Research Journal, 2020)
In this text we present a discussion on some theoretical models that support the study of educational organizations, focusing on bureaucratic and anarchic models in an integrative perspective, dual, supported by the diptych mode of operation proposed by Lima [9],[10]. The study aims to present sociological perspectives for the understanding and interpretation of educational organizations focusing on bureaucratic and anarchic models. It is, therefore, a theoretical essay of qualitative approach, based on bibliographical research as the theoretical support.